2006
DOI: 10.1007/s10549-006-9222-z
|View full text |Cite
|
Sign up to set email alerts
|

GnRH analogs reduce invasiveness of human breast cancer cells

Abstract: These data represent the first report that the activation of tumor GnRH receptors reduces the metastatic potential of breast cancer cells. The crosstalk between metastatic breast cancer cells and bone is critical to the development and progression of bone metastases. Disruption of this interaction will allow us to design mechanism-based effective and specific therapeutic interventions for bone metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 43 publications
1
51
0
2
Order By: Relevance
“…In different breast cancer cells lines (HCC70, MCF-7, MDA-MB-435, MDA-MB-453 and T47-D), their invasive capability was increased when these were co-cultured with hOB or MG63 osteosarcoma cells. This effect was reverted after GnRH analog treatments, demonstrating receptor ability to down-regulate cell motility in this cellular model (130) (Fig. 2D).…”
Section: Gnrhr and Ovarian Cancermentioning
confidence: 80%
“…In different breast cancer cells lines (HCC70, MCF-7, MDA-MB-435, MDA-MB-453 and T47-D), their invasive capability was increased when these were co-cultured with hOB or MG63 osteosarcoma cells. This effect was reverted after GnRH analog treatments, demonstrating receptor ability to down-regulate cell motility in this cellular model (130) (Fig. 2D).…”
Section: Gnrhr and Ovarian Cancermentioning
confidence: 80%
“…Previous work had shown that breast cancer cell invasion through an artificial basement membrane in vitro was increased by coculture with human primary osteoblasts (hOB) or osteoblast-like sarcoma cells [19]. The ability to invade the basement membrane and to migrate in response to the cellular stimulus was significantly reduced after treatment with GnRH-I/-II analogs [19].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we demonstrated that GnRH-II antagonists bind to the GnRH-I receptor and are clear antagonists at the GnRH-I receptor [17]. Recently, we showed that invasion of breast cancer cells through an artificial basement membrane was increased when they were cocultured with human primary osteoblasts (hOB) [19]. The ability to invade the basement membrane and to migrate in response to the cellular stimulus was significantly reduced after treatment with GnRH analogs [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The GnRH system has been reported to play an autocrine/paracrine role in the inhibition of cellular growth and metastatic potential in breast cancer cell lines [24,35], and breast tumor regression in nude mouse [14,26]. However, its expression was associated with a protective effect on the chemotherapeutic drug-produced apoptosis [30].…”
Section: Introductionmentioning
confidence: 99%